Community management for the promotion of the rights of minors in the Canton of Santa Bárbara de Heredia, Costa Rica - Rivera Alfaro, Ronald (2025)
This article systematizes the institutional experience developed in the canton of Santa Bárbara de Heredia for the elaboration of the cantonal policy for minors (PME), in which an institutional commitment to associative work was articulated between institutionalized community organizations, the local government, the National Children’s Trust, the Ministry of Public Education, and the National University. In this way, it presents the reconstruction and analytical reflection of a communal experience in a community management process based on the regulatory structure that allows for participatory local development under the precepts of the needs and interests of the population. Methodologically, this process was carried out from a qualitative approach, systematizing experiences through the application of online surveys via the LimeSurvey platform with a battery of 28 questions for PME attending primary school and 40 questions for PME attending secondary school. In both cases, the questions were divided into eight categories based on the four pillars that structure the Code for Children and Adolescents ‒survival, development, protection, and participation‒ with a total of 1,383 minors between the ages of 7 and 18 participating. The categories used to organize the survey were: right to freedom of opinion; right to identity and nationality; right to family; right to food; right to health care; teenage pregnancy; right to free education; and right to culture, recreation, and sports. Participatory workshops were also held for community leaders and families from different districts in the canton. The information collected was analyzed using thematic coding and interinstitutional triangulation. The main findings identified widespread perceptions of insecurity, family fragmentation, low child participation in family and community decisions, and worrying exposure to social risk factors. The need to strengthen local protection networks, child participation mechanisms, and inter-institutional coordination was evident. In conclusion, it is reaffirmed that community management with an inter-institutional approach is an effective way to design public policies aimed at protecting children’s rights, strengthening community training, and guaranteeing public budgets with a rights-based approach. This systematization demonstrates the potential of university outreach to stimulate transformative social action at the local level.